The Influence of Brand Ambassador and Content Marketing on Decisions to Purchase Ultra Milk Products (Case Study of Instagram Users in Surabaya) - Putri, Betaria Novila Ananda; Fitriyah, Zumrotul (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study was conducted to determine and understand how Brand Ambassadors and content marketing affect consumer purchasing decisions to buy Ultra Milk milk. In the current era, many companies use K-pop Brand Ambassadors and content marketing to promote their products on social media platforms, one of which is Instagram. It is hoped that this research will be useful as a reference in future research. The method used in this study uses SEM techniques with a quantitative approach and purposive sampling method using a Likert scale. The results showed that the Brand Ambassador variable did not have a significant influence on purchasing decisions. In contrast to the content marketing variable which has a significant influence. The implication of the results of this study is the importance of companies in optimising the role of Brand Ambassadors in marketing Ultra Milk milk products and maintaining and developing Content Marketing strategies.